Juridical Review of the Criminalization of Perpetrators of Sexual Violence Against Children (Study of Decision Number: 815/Pid.Sus/2025/PN.Tjk) - Maharani Boruregar; Sunarto; Andriansyah Kartadinata (PALAR | PAKUAN LAW REVIEW, 2026)
Abstract Sexual violence against children constitutes a serious crime that causes long-term physical, psychological, and social harm and requires optimal legal protection through the criminal justice system. This study aims to analyze the application of criminal law and the judge’s considerations in sentencing perpetrators of sexual violence against children based on Decision of the Tanjung Karang District Court Number 815/Pid.Sus/2025/PN.TJK. The research employs normative juridical and empirical juridical approaches by examining relevant laws and regulations as well as analyzing court decisions. The results indicate that the judges appropriately applied the elements of the criminal offense and considered child protection aspects, evidentiary factors, the condition of the perpetrator, and the impact on the victim. The sentencing imposed in the decision fulfills the principles of legal certainty, justice, and expediency. Nevertheless, strengthening regulations and enhancing the capacity of law enforcement officers remain necessary to ensure comprehensive handling of cases of sexual violence against children and to prioritize victim protection. Keywords: punishment, sexual violence, children, child protection, judicial considerations